Experimental research on bypass evaporation tower technology for zero liquid discharge of desulfurization wastewater. Issue 20 (6th September 2019) - Ma, Shuangchen; Chai, Jin; Wu, Kai; Xiang, Yajun; Jia, Shaoguang; Li, Qingsong
ABSTRACT: Zero liquid discharge (ZLD) of wastewater has become the trend of environmental governance after the implementation of 'The Action Plan for Prevention and Treatment of Water Pollution' in China, desulfurization wastewater has gained more attention due to its complex composition and heavy metals. However, current technologies for ZLD have some shortcomings such as high cost and insufficient processing capacity, ZLD cannot be achieved actually. This paper proposes a new evaporation drying technology. An independent bypass evaporation tower was built, part of the hot flue gas before the air preheater was introduced into the evaporation tower for desulfurization wastewater evaporation, and the generated dust after evaporation was discharged back to the flue duct before electrostatic precipitator. This paper reports on the performance of desulfurization wastewater evaporation and the characteristics of evaporation products in depth and makes a comprehensive discussion of the impact on the existing equipment based on the self-designed evaporation tower. Research suggests that this technology has high system reliability and little effect on subsequent equipment and provides theoretical and practical data. Due to environmental policies and huge market demand for ZLD of desulfurization wastewater, bypass evaporation tower technology has a great application prospect in the future.